Comb segmentation spectroscopy for rapid detection of molecular absorption lines - Lee, Jaehyun (2019)
We perform fast comb spectroscopy by dividing the probe comb into several sub-comb segments so as to produce multi-heterodyne beats focused around targeted molecular absorption lines. This concentrated scheme of comb spectroscopy is able to achieve a 30 dB signal-to-noise ratio with just a single shot measurement of 10 μs acquisition time. Such high signal sensitivity is verified by measuring separate absorption lines of H13C14N and 12CO2 gases simultaneously. In addition, atmospheric 12CO2 concentration over a 1.3 km open-air path is traced with a signal repeatability of 15 ppm at a 5 kHz update rate.